2003
DOI: 10.2355/isijinternational.43.1767
|View full text |Cite
|
Sign up to set email alerts
|

Flow Injection Analysis of Phosphorus in Steel Using Filter Tube Preconcentration

Abstract: A flow injection analysis (FIA) of phosphorus using coprecipitation with beryllium hydroxide was performed. An on-line preliminary concentration method using a filter tube was developed and this method was applied to the determination of phosphorus in steel. Phosphorus was coprecipitated with beryllium hydroxide by increasing the pH of the medium in the flow tube, and the precipitate was collected with the filter tube (pore size: 1.0 mm, inner diameter: 1.0 mm, length: 7 cm). The precipitate collected was elut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 12 publications
0
1
0
1
Order By: Relevance
“…1b, still remained. 46 Other studies also suggested that easily diffusive hydrogen is essential for the occurrence of failure at least under mild environments. 46 -48 Easily diffusive hydrogen consists of lattice hydrogen and weakly trapped hydrogen.…”
Section: Effect Of Hydrogenmentioning
confidence: 99%
“…1b, still remained. 46 Other studies also suggested that easily diffusive hydrogen is essential for the occurrence of failure at least under mild environments. 46 -48 Easily diffusive hydrogen consists of lattice hydrogen and weakly trapped hydrogen.…”
Section: Effect Of Hydrogenmentioning
confidence: 99%
“…Namun, proses ekstraksi yang membutuhkan waktu lama dan jumlah pelarut yang banyak menyebabkan metode ini tidak efektif dan efisien dalam analisis. Proses ekstraksi dapat diganti dengan proses automasi yang lebih cepat, efektif dan efisien yang disebut dengan teknik prakonsentrasi analisis injeksi alir (flow injection analysis) [1][2][3][4][5][6][7][8] . Teknik injeksi alir merupakan metode analitik yang didasarkan pada penginjeksian sejumlah sampel dalam bentuk larutan ke dalam suatu aliran tidak bersegmen.…”
Section: Pendahuluanunclassified